Respons Mahasiswa terhadap Bahan Ajar Keterampilan Menyimak - Lazuardi, Dian Ramadan; Effendi, M. Syahrun; Murti, Sri (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
Student responses to Listening Skills teaching materials are carried out to determine the feasibility of teaching materials for use in learning. The purpose of this study was to describe the responses of Indonesian Language and Literature education students to Listening Skills teaching materials. The formulation of the problem in this study is how the response of students of Indonesian Language and Literature education to the Listening Skills teaching materials based on a scientific approach. This study used a quantitative descriptive method. Data collection in this study used a questionnaire. The data analysis technique is by carrying out the stages: description, classification, analysis, data interpretation, evaluation, and conclusions. Based on the results of the study it was found that the response of Indonesian Language and Literature students to the Listening Skills teaching materials was positive with an average percentage of 72.10%, Students liked the Listening Skills teaching materials, the Listening Skills teaching materials were interesting and fun, the language used in the teaching materials was easy to understand, and teaching materials for listening skills according to what students expect. It can be concluded that the Listening Skills material can motivate learning activities and this teaching material is feasible to use.